Implementation of Democracy in the Village: A Case Study of Village Deliberation in Ciheulang Village - Syarifah, Najwa Auliya; Rahmani, Allyah Nur; Addinari, Shabina Sundus (JURNAL MAHASISWA YUSTISI, 2025)
Village deliberation (musyawarah desa) serves as the highest forum in the village to discuss, formulate, and decide policies related to development, planning, and strategic village issues. This forum plays a vital role in actualizing participatory democracy at the local level. This study aims to analyze the implementation of democratic values in the village deliberation of Ciheulang Village, Bandung Regency. Using a qualitative case study method, data were collected through interviews and documentation. The results show that the participation rate in Ciheulang’s village deliberations is relatively high, reflecting a strong democratic tradition rooted in communal culture. However, the process still faces challenges, such as uneven representation and tendencies toward one-way communication. This study concludes that democratic implementation at the village level requires continuous enhancement of transparency, inclusiveness, and critical participation from all societal elements.